Influence of ferroptosis indicators on the stability of atherosclerotic plaque: Ferroptosis Indicators and Atherosclerotic Plaque Stability - Guo, Hong; Zhang, Aobo; Qiu, Lei; Mao, Jianhui; Zheng, Lei; Zhao, Zongmao (Cellular and Molecular Biology, 2023)
Ferroptosis is a new form of cell death that is unique and closely related to iron concentration, and reactive oxygen species (ROS) production. We investigated the indicators of ferroptosis between vulnerable plaque and stable plaque in atherosclerotic. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting were used to detect the expression of the ferroptosis-related genes and proteins and extracellular matrix stability-related genes and proteins (FN, CoL-1). Superoxide dismutase (SOD) activities, glutathione peroxidase (GSH) and malondialdehyde (MDA) were detected by ELISA. The commercially available kit was used to detect Fe2+ concentration in tissue. DCFH-DA fluorescent probe was used to detect the ROS levels. H&E stain, Masson trichrome stain, and Oil Red O stain were used to detect pathological states in vulnerable plaque and stable plaque. Tissue localization and positive rate of GPX4, SLC7A11, COX-2, FN, and COL-1 were evaluated by immunohistochemistry. The results showed a significant increase in the expression of COX2 and a significant decrease in the expression of GPX4 and SLC7A11 in genes related to ferroptosis in vulnerable plaque compared with stable plaque. Pathologic results showed vulnerable plaque with higher levels of inflammatory cell infiltration, more diffuse collagen fibers, and larger particles of lipid droplets. Concentrations of the antioxidant metabolites SOD and GSH were significantly reduced and concentrations of the oxidative metabolites MDA and Fe2+ were significantly increased in vulnerable plaque compared with stable plaque. The expression of FN and CoL-1 was significantly reduced in genes related to extracellular matrix stability in vulnerable plaque. Taken together, these findings indicate that the degree of ferroptosis in vulnerable plaque is higher than that in stable plaque, suggesting that changes in indicators of ferroptosis may affect carotid atherosclerotic plaque stability, target spot in the ferroptosis signaling pathway may provide further theoretical basis for the clinical treatment of carotid atherosclerosis.